High power downconversion deep-red emission from Ho3+-doped fiber lasers - Ji Shuaihao; Song Yingyi; Wang Zhongyu; Shen Chenyao; Lin Jiazhen; Xiao Bo; Feng Qichen; Du Qingyang; Xu Huiying; Cai Zhiping (Nanophotonics, 2022)
It has been a big challenge in decades for Ho3+-doped fiber laser to produce high emission power in deep-red due to its intrinsic long carrier lifetime in 5I7 energy level. Here, we advance the development of this visible fiber lasers by a novel pumping method that leverages the advantages of blue laser diode downconversion mechanisms to fully pumping, while shortening the lifetime of the lower energy level of the deep-red laser through excited state absorption. For the first time, we demonstrate a downconversion fiber laser using a single wavelength of 532 nm solid-state laser pump source to excite the Ho3+-doped ZBLAN fiber, which achieves a record high maximum output power of 1.64 W at 752.10 nm, as well as free-running of deep-red lasers with watt-level output. This technology represents a milestone in high power deep-red fiber lasers. Importantly, it is readily to be extended to other wavelengths that evidenced its huge application potentials in fiber laser industry.